2014
DOI: 10.1021/es503751v
|View full text |Cite
|
Sign up to set email alerts
|

SphagnumMosses from 21 Ombrotrophic Bogs in the Athabasca Bituminous Sands Region Show No Significant Atmospheric Contamination of “Heavy Metals”

Abstract: Sphagnum moss was collected from 21 ombrotrophic (rain-fed) peat bogs surrounding open pit mines and upgrading facilities of Athabasca bituminous sands in Alberta (AB). In comparison to contemporary Sphagnum moss from four bogs in rural locations of southern Germany (DE), the AB mosses yielded lower concentrations of Ag, Cd, Ni, Pb, Sb, and Tl, similar concentrations of Mo, but greater concentrations of Ba, Th, and V. Except for V, in comparison to the "cleanest", ancient peat samples ever tested from the nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
116
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 34 publications
10
116
0
2
Order By: Relevance
“…Although fossil fuel combustion has increased since some early studies on V atmospheric deposition (e.g., (Duce and Hoffman, 1976;Zoller et al, 1973)), controls on emissions in some countries have reduced the inputs of V to the atmosphere, which is reflected by lower rates of land deposition (Cloy et al, 2011;Harmens et al, 2007). Elevated concentrations of V in Sphagnum moss collected from rain-fed peat bogs near the Athabasca oil sands in Alberta, Canada support, however, that emissions from mining and processing bitumen do still contribute to increased land deposition of V locally (Shotyk et al, 2014).…”
Section: Vanadium In the Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…Although fossil fuel combustion has increased since some early studies on V atmospheric deposition (e.g., (Duce and Hoffman, 1976;Zoller et al, 1973)), controls on emissions in some countries have reduced the inputs of V to the atmosphere, which is reflected by lower rates of land deposition (Cloy et al, 2011;Harmens et al, 2007). Elevated concentrations of V in Sphagnum moss collected from rain-fed peat bogs near the Athabasca oil sands in Alberta, Canada support, however, that emissions from mining and processing bitumen do still contribute to increased land deposition of V locally (Shotyk et al, 2014).…”
Section: Vanadium In the Atmospherementioning
confidence: 99%
“…Liquid waste and wash water from plants may contain up to several hundred mg L 1 V. Other industries that generate V-containing wastes include the chemical and polymer industry, where V is an important component in a wide array of chemical syntheses and oxidation reactions, and the mining industry, where the processing of U and Ti ores produces V-containing effluents and leachates (Nriagu, 1998). Additional V is released to surface environments by fossil fuel processing and burning, mining activity, and the application of phosphorous fertilizers (Aide, 2005;Nakano et al, 1990;Shotyk et al, 2014). The combustion of V-enriched fossil fuels in par-…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%
“…The Alberta Government (2010) concluded, "there has been no increase in concentrations of contaminants as oil sands development has progressed." Other studies have also reported minimal impacts of development (e.g., Shotyk et al 2014;Wiklund et al 2014). These studies standardized their data using lithophilic elements as tracers (critiqued by Blais and Donahue 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These studies standardized their data using lithophilic elements as tracers (critiqued by Blais and Donahue 2015). However, lithophilic elements such as lithium (Li) (Wiklund et al 2014) and thorium (Th) (Shotyk et al 2014) are also associated with a range of industrial applications pervasive to the oil sands region (see CRC 1982), and may therefore be unsuitable geochemical tracers.…”
Section: Introductionmentioning
confidence: 99%
“…피트모스는 보수력 (Hu et al, 2009;MacCarthy, 1976) 및 유기물 함량이 높고, 다양한 영양소를 포함하고 있어서 식물의 성장촉진제 또는 비료 대체제로서 많이 이용된다 (Hu et al, 2009;MacCarthy, 1976). 그러나 피트모스의 성분은 생산지 (Shotyk et al, 2014), 분해시간 (Shotyk et al, 2014) 및 추출방법 (Ali et al, 2012;Marquez-Reyes et al, 2013;Kim et al, 2011)등에 따라 큰 차이가 있는 것으로 알려져 있다.…”
unclassified